Men with HIV have increased alveolar bone loss - Michelle Skelton; Cameron Callahan; Michael Levit; Taylor R. Finn; Karolina Kister; Satoko Matsumura; Anyelina Cantos; Jayesh Shah; Sunil Wadhwa; Michael T. Yin (BMC, 2024)
Abstract Background Periodontal health in men with HIV remains understudied, despite suggestions of associations between HIV infection and gingival pocketing, periodontal attachment loss, and gingival inflammation. As antiretroviral therapy (ART) has improved the quality of life for people living with HIV (PLWH), aging-related risk factors and comorbidities, including periodontitis, have emerged. This study aims to assess alveolar bone height, gingival crevicular fluid (GCF) cytokines, and periodontal disease activity in men with and without HIV. Methods Ninety-three men (50 HIV+, 43 HIV-) aged 35-70 years were recruited from Columbia University Irving Medical Center clinics. Periodontal examination, GCF collection, and intraoral radiographs were collected. Statistical analysis was conducted with t-tests for continuous variables and chi-squared tests for categorical variables. Results While no significant differences were observed in bleeding on probing, clinical attachment loss and pocket depths, men with HIV exhibited significantly greater alveolar crestal height on radiographs compared to men without HIV (HIV + 3.41+/-1.35 mm, HIV- 2.64+/-1.01 mm; p = 0.004), reflecting greater alveolar bone loss. Conclusions Men living with HIV demonstrate increased alveolar bone loss compared to those without HIV, possibly mediated by elevated IL6 levels. These results underscore the importance of comprehensive oral health management in PLWH and highlight the need for further research understanding the mechanisms linking HIV infection, cytokine dysregulation, and periodontal health.